Novel mutation in XPNPEP3 in a patient with heart failure without nephronophthisis-like nephropathy (NPHPL1): case report and literature review - Zhen Zhen; Ziyan Dong; Lu Gao; Qin Wang; Xi Chen; Jia Na; Yue Yuan (BMC, 2024)
Abstract Background X-prolyl aminopeptidase 3 (XPNPEP3) mutations are known to cause nephronophthisis-like nephropathy-1 (NPHPL1), a rare autosomal-recessive kidney disease characterized by progressive kidney failure and cystic kidney disease in childhood. The full phenotypic spectrum associated with mutations in XPNPEP3 is not fully elucidated. Case presentation A 13-year-old Chinese female patient with intellectual disability presented with a 2-year history of convulsions and fatigue, with a recent episode of swelling, breathlessness, and nocturnal dyspnea lasting 10 days. The patient was diagnosed with heart failure and kidney failure. Whole exome sequencing revealed a homozygous c.970-2 A > G mutation in XPNPEP3 associated with severe cardiac dysfunction and neurological symptoms, including epilepsy and intellectual disability. Notably, kidney ultrasound did not reveal the typical changes of NPHPL1, and kidney failure was hypothesized to be secondary to cardiac dysfunction rather than primary kidney pathology. Conclusions This case suggests the possible association of additional phenotypic features associated with XPNPEP3 mutations, emphasizing the need for further investigation into the heterogeneous clinical presentations associated with XPNPEP3 mutations. The findings highlight the importance of considering alternative phenotypes in patients with genetic mutations traditionally associated with specific diseases. Segregation and functional analyses are necessary to determine causality between the c.970-2 A > G XPNPEP3 mutation and disease.